Legal Certainty in the Regulations Regarding the Prohibition of Notaries from Serving as Leader of Private Business Entities - Yuni Aisyatun Nailah; Amelia Sri Kusuma Dewi; Diah Aju Wisnuwardhani (Rescollacom (Research Collaborations Community), 2025)
Legal certainty in a regulation will create order. If every individual or law enforcer can interpret a regulation properly and clearly, then a regulation will run as it should. One of the prohibitions stipulated in Article 17 paragraph (1) letter f UUJN is the prohibition for notaries to hold concurrent positions as leaders of private business entities. The concept of a leader in various types of private business entities covers a broad role, from strategic decision-making to operational management. Interpretations of who is considered a